The Need to Academically Redefine the Work of Cinematographers in Film (Andamios, Revista de Investigación Social, 2024)
Cinematographers are responsible not only for the camera operation and lighting of a film, but thanks to their cultural background, their knowledge of cinematographic language and their artistic sensibility, they collaborate with the director of a film in the aesthetic conception. and narrative of it. Based on a comparative study on indexed database sites such as Scopus, Web of Science, REDALYC or SCIELO, will try to emphasize the disproportionate amount of texts where the directors are cited as the only authors of the film and made cinematographers conceptual and artistic works invisible in the academic world.
Keywords: Cinematographer; director; academics; artistic; author